2023
DOI: 10.3389/fpls.2023.1189005
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of terminal heat stress on contrasting wheat cultivars: a comprehensive analysis of phenological, physiological, and biochemical traits

Hitesh Kumar,
Vishal Chugh,
Manoj Kumar
et al.

Abstract: Terminal heat stress has become one of the major threats due to global climate change which is significantly affecting the production and productivity of wheat crop. Therefore, it is necessary to identify key traits and genotypes to breed heat-tolerant wheat. The present study was undertaken with the objective of comparing the effects of heat stress (HSE) and extended heat stress (EHSE) on phenological-physio-biochemical traits of contrasting heat-tolerant and heat-susceptible genotypes during the reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 95 publications
1
1
0
Order By: Relevance
“…2018; Abdelrahman et al 2020a, b; Janni et al 2020; Lal et al 2021; Shokat et al 2023). Furthermore, the BY and HI showed positive direct contributions to GY under the severe heat stress (VLS scenario), which is in conformity with a recent study where BY along with DTM have been shown to be the signi cant contributors to GY under heat stress(Kumar et al 2023a).…”
supporting
confidence: 91%
“…2018; Abdelrahman et al 2020a, b; Janni et al 2020; Lal et al 2021; Shokat et al 2023). Furthermore, the BY and HI showed positive direct contributions to GY under the severe heat stress (VLS scenario), which is in conformity with a recent study where BY along with DTM have been shown to be the signi cant contributors to GY under heat stress(Kumar et al 2023a).…”
supporting
confidence: 91%
“…This augmentation ultimately leads to higher tolerance against abiotic stressors, as evidenced by Lee et al [ 45 ]. Numerous research studies have emphasized the importance of strengthening the antioxidant defense system, which includes antioxidant enzymes and metabolites, combating oxidative stress; notably, key detoxifying enzymes such as SOD, POX, and CAT work in collaboration with APX and GR within the ascorbate–glutathione cycle, aiding in the elimination of ROS during abiotic stress episodes [ 5 , 9 , 34 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%